The first clinical experience of Marshall’s vein alcohol ablation in complex treatment of persistent atrial fibrillation - V.V. Boiko; S.V. Rybchynskyi; D.O. Lopin; A.S. Vnukova; D.Ye. Volkov (Кардіохірургія та інтервенційна кардіологія)
This article describes the first in Ukraine clinical experience of alcohol ablation of Marshall’s vein in the complex interventional treatment of persistent atrial fibrillation (AF). Current scientific data suggest that when drug therapy is ineffective, ablation of AF substrate is a most important stage in the treatment of arrhythmia, as well as optimal method of control and prevention of further cardiovascular events. The standard treatment for paroxysmal AF is radiofrequency ablation (RFA) with electrical isolation of the pulmonary veins (PVI). However, due to the involvement of other pathogenetic mechanisms, a sole PVI is less effective in persistent forms of arrhythmia. For example, in persistent AF forms pathological electrical activity often occurs beyond the pulmonary veins. In particular, it can be observed in the area of ​​the posterior wall of the left atrium and mitral isthmus resulting in perimitral atrial flutter. RFA in this area can reduce the rate of arrhythmia recurrence. However, achieving a stable bidirectional conduction block in the area of ​​lateral mitral isthmus with endocardial RFA is technically challenging. An option to improve the effectiveness of RFA in this case, apart from epicardial RFA in the distal coronary sinus, is an alternative method, i.e. alcoholic ablation of Marshall’s vein by introducing ethanol into its lumen, occluded by a balloon. The presented clinical case shows combined variant of persistent AF minimally invasive treatment using alcoholic Marshall’s vein ablation and RFA with PVI target.